Divide and Conquer: How Conquering Multiple Niches Influenced the Evolution of the Divided Bacterial Genome - diCenzo, George Colin (My University, 2017)
Approximately 10% of sequenced bacterial genomes are multipartite, consisting of two or more large chromosome-sized replicons. This genome organization can be found in many plant, animal, and human pathogens and symbionts. However, the advantage of harbouring multiple replicons remains unclear. One species with a multipartite genome is Sinorhizobium meliloti, a model rhizobium that enters into N2-fixing symbioses with various legume crops. In this work, S. meliloti derivatives lacking one or both of the secondary replicons (termed pSymA and pSymB) were constructed. Phenotypic characterization of these strains, including growth rate, metabolic capacity, and competitive fitness, provided some of the first experimental evidence that secondary replicons evolved to provide a niche specific advantage, improving fitness in a newly colonized environment. These results were further supported by characterizing the symbiotic phenotypes of 36 large-scale pSymA and pSymB deletion mutants. To further this analysis, an in silico S. meliloti genome-scale metabolic network reconstruction was developed and flux balance analysis used to examine the contribution of each replicon to fitness in three niches. These simulations were consistent with the hypothesis that metabolic pathways encoded by pSymB improve fitness specifically during growth in the plant-associated rhizosphere. Phylogenetic analysis of a pSymB region containing two essential genes provided a clean example of how a translocation from the primary chromosome to a secondary replicon can render the secondary replicon essential. Moreover, an experimental analysis of genetic redundancy indicated that 10-15% of chromosomal genes are functionally redundant with a pSymA or pSymB encoded gene, providing an alternative method for how secondary replicons can become essential and influence the evolution of the primary chromosome. Finally, the work presented here provides a novel framework for forward genetic analysis of N2-fixing symbiosis and the identification of the minimal N2-fixing symbiotic genome, which will help facilitate the development of synthetic symbioses.
Keywords: Multipartite genome; Divided genome; Chromosome; Chromid; Megaplasmid; Genome evolution; Sinorhizobium meliloti; Symbiotic nitrogen fixation; Bacterial genetics; Systems biology; Metabolic modelling; Genome engineering